Effects of post-annealing on the dielectric properties of Au/BaTiO3/Pt thin film capacitors - Lee, EJH; Pontes, F. M.; Leite, E. R.; Longo, Elson [UNESP]; Magnani, R.; Pizani, P. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Barium titanate thin films were prepared by the polymeric precursor method and deposited onto Pt/Ti/SiO2/Si substrates. X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FT-IR) and micro-Raman spectroscopy were used to investigate the formation of the BaTiO3 perovskite phase. Afterwards, the films were submitted to post-annealing treatments in oxygen and nitrogen atmospheres at 300 degreesC for 2 h, and had their dielectric properties measured. It was observed that the electric properties of the thin films are very sensitive to the nature of the post-annealing atmosphere. This study demonstrates that post-annealing in an oxygen atmosphere increases the dielectric relaxation phenomenon and that post-annealing in a nitrogen atmosphere produces a slight dielectric relaxation. (C) 2004 Elsevier B.V All rights reserved.
Keywords: barium titanate; dielectric properties; conduction mechanism; post-annealing